Faith-based agency and theological education: A failed opportunity? - Beer, Stephan F. de (HTS teologiese studies, 2019)
After attending to shifts in the landscape of theological education at a public university in South Africa, this article explores the re-imagination of theological education as fostering faith-based agency. With reference to the (potential) role faith-based organisations play in response to developmental challenges in local communities, it then suggests a deliberate retrieval of faith-based sources – locatedness, voices, assets, agency and formation – in liberating theological education. It concludes with concrete curriculum recommendations for consideration.